Fuselage Weight Estimation in Conceptual Design Phase for Tactical Unmanned Aerial Vehicles (المجلة الدولية للبحوث العلمية, 2023)
Fuselage weight Estimation of an Unmanned Aerial Vehicle (UAV) during the conceptual design phase has been demonstrated to be an important challenge because of its unconventional configuration. Investigation of the development of a new suggested formula for fuselage weight estimation of UAV is done for UAVs having takeoff weight ranging from 100 to 500 kg, and which have similar characteristics. Based on statistical trends, obtained from analyzed existing UAVs, takeoff weight is estimated from mission specification, and it is derived for a tactical unmanned aerial vehicle (TUAV). Software tools are developed in MATLAB to facilitate takeoff and component weight calculations. The least square method is applied to analyze statistical data in order to develop trend functions which correlate TUAVs takeoff weight. Existing formulas, developed for general aviation, for fuselage and takeoff weight estimations are applied to TUAV and promising one are selected and adjusted to TUAV conceptual design phase. Fuselage weight estimation is related to geometrical parameters and takeoff weight of TUAVs.